QIM, CATA, and Word Association methods for quality assessment of flathead gray mullet (Mugil cephalus): Going beyond the trained panel - Tiyo de Godoy, Nathália; Veneziano, Andre Luis; da Cunha Rodrigues, Larissa; Schoffen Enke, Dariane B. [UNESP]; Lapa-Guimarães, Judite (Wiley, 2019)
This study aimed to verify how untrained assessors would perform the quality evaluation of the flathead gray mullet (Mugil cephalus) using Check-All-That-Apply (CATA) (n = 44) and Word Association (WA) (n = 112) methods by comparing the results with those from trained assessors (n = 5–9), using the Quality Index Method (QIM). Descriptors from QIM were adapted and used as CATA descriptors for the evaluation of fish with 3, 8, 10, 15, and 17 days of storage in ice. Images of fish with 3, 6, 10, 15, and 19 days of ice storage were used as stimuli for WA. The quality indices obtained from QIM and CATA presented a high correlation with r =.94 (p =.018). Multiple Factor Analysis revealed a high similarity between CATA and QIM sample configurations. Appropriate descriptors were selected in CATA for fish stored for different periods. This resulted in a better discrimination of samples in comparison with WA. M. cephalus, with 15 days of storage in ice, was rated unacceptable for consumption by both trained and untrained assessors. These findings showed that even untrained assessors were able to evaluate fish freshness, and thus emphasize the importance of actions aimed at maintaining the quality of raw fish from capture to commercialization. Practical applications: The evaluation of fish quality by consumers has been considered tricky. Only more experienced fish consumers have confidence in their ability to judge the freshness of fish. However, our study showed that untrained individuals, confronted with the task of evaluating fish quality using both the CATA and the Word Association methods, performed very well. This allowed us to conclude that they were clearly able to evaluate freshness. Untrained individuals were neither stricter, nor more lenient than trained assessors in determining the shelf life of the flathead gray mullet. Our study joined many others that have concluded that CATA method—thanks to its easiness to perform—resulted in the discrimination of samples similar to that obtained with trained panels. These findings demonstrate that CATA and WA methods, designed to be applicable with untrained panels, were effective in the evaluation of fish freshness, thus providing a solution when trained assessors are not available. In addition, the importance of trading fish with high quality is clear, so that the consumers can receive value for their money and feel satisfied.